Scalable Uncertainty Management 5th International Conference, SUM 2011, Dayton, OH, USA, October 10-13, 2011, Proceedings - Benferhat, Salem; Grant, John (Lecture Notes in Artificial Intelligence, 2011)
This book constitutes the refereed proceedings of the 5th International Conference on Scalable Uncertainty Management, SUM 2011, held in Dayton, OH, USA, in October 2011. The 32 revised full papers and 3 revised short papers presented together with the abstracts of 2 invited talks and 6 "discussant" contributions were carefully reviewed and selected from 58 submissions. The papers are organized in topical sections on argumentation systems, probabilistic inference, dynamic of beliefs, information retrieval and databases, ontologies, possibility theory and classification, logic programming, and applications.